Diagnosis of parasitic infections in vermiform appendix in patients with appendicitis in Kirkuk city, Iraq - Khulood Abdulmuttaleb Al-Saeedi; Fatima Shihab Al-Nasiri (Tikrit Journal of Pure Science, 2019)
The present study is conducted in Kirkuk city, Iraq; between July to December 2018. Within this period 197 resected appendix are examined to investigate the parasitic infections that may associated with appendicitis. Direct with concentrated methods are used in luminal content examinations. Also, histological examination of haematoxylin and eosin stained tissue sections is performed to diagnose the parasitic infections in the lumen and within the appendix tissue. The parasitic infection reported in 12.69% cases included four species, as well as a mixed infection. Entamoeba histolytica (trophozoite and cyst), Giardia lamblia (trophozoite and cyst), Cryptospordium sp.(oocyst) and Enterobious vermicularis (adult worm and ova) are recorded. The most common determined parasite is E. histolytica (8.63%). The parasitic infection within the resected appendix reported in females (8.12%) more than males (4.57%). The parasitic infections in the study are prevalent in patients within the age groups 13 to 18 years and 19 to 24 years (3.55% for each one).